Spontaneous Second Intercostal Artery Bleeding Complicated with Massive Hemothorax after Lower Limb Angioplasty Procedure - Al-Ataby, Harith (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.